Economics of using combine harvesters in the mechanized rainfed schemes of eastern Sudan - A. Yousif, Lotfie; H. Babiker, Ebtehag (Gezira Journal of Agricultural Science; Vol 16 No 2 (2018), 2018)
The effective use of combine harvesters not only needs knowledge about operation requirements, but also needs economic evaluation. The objective of this study was to make economic analysis for combine harvesters used in harvesting mechanized rainfed schemes in eastern Sudan. The data were collected from combine harvesters owners through a comprehensive questionnaire that covered 23 combine harvesters in 2016/2017 season. The collected data included fixed cost items such as purchase price, insurance, shelter and taxes and variable cost items like repair and maintenance, fuel, oil, drivers and supervision. Also, data on harvester working parameters like annual harvested area and working hours, besides custom hiring price and crop yield, were collected. In addition to cost analysis, the breakeven point (BEP), in terms of hectares that have to be harvested annually to cover annual fixed costs; and the payback period (PBP) were calculated. Also, sensitivity analyses were carried out to detect the effect of changing cost parameters on BEP and PBP. The results indicated that the annual harvested area by a combine harvester was found to be 1525 ha in 623 hours. The average fixed cost was found to be 207.5 SDG/ha, which constituted about 16.8% and 68.5% of the purchase price and total operating cost, respectively. Whereas the average variable cost was 95.4 SDG/ha, representing 7.7% and 31.5% of the purchase price and total operating cost, respectively. The results indicated that the depreciation cost was the highest among the fixed cost items and fuel cost was the highest among the variable cost items. The results showed that the average cost for direct harvesting operation was 303 SDG/ha (742.1 SDG/hr). It was found that the BEP was 904 ha and the PBP was 9 years. The sensitivity analysis revealed that increasing the purchase price will increase both the BEP and PBP. The study concluded that the use of a combine harvester in the mechanized rainfed schemes for direct harvesting was profitable for both farmer and investor. When the annual required areas by the combine harvester was satisfied, the estimated profit was 143 SDG/ha. However,it is not advisable to use direct harvesting when crop yield is lower than 450 kg/ha.